2018
DOI: 10.1111/jvh.12898
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and phylodynamic analyses of hepatitis C virus subtype 1a in Okinawa, Japan

Abstract: Okinawa Island, located in Southern Japan, has a higher prevalence rate of hepatitis C virus subtype 1a (HCV-1a) infection than that in mainland Japan. Okinawa has a history of US military occupation after World War II. To elucidate the transmission history of HCV-1a in Okinawa, 26 whole-genome sequences were obtained from 29 patients during 2011-2016. Phylogenetic trees were reconstructed to identify the origin and characteristics of HCV-1a in Okinawa with epidemiological information. A phylogenetic tree base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Phylodynamic analysis was performed on concatenated NS3, NS5A, and NS5B sequences of every patient in order to increase the confidence of inferred evolutionary relationships. Several studies have tried to reconstruct the origin and evolutionary history of the most common epidemic HCV subtypes such as GT1a, GT1b, and GT3a [ 4 , 32 , 50 , 56 , 57 , 58 , 59 ]. A study by Margiokinis et al (2009) supports a massive expansion of the GT1a and GT1b epidemics between 1940 and 1980, with the expansion of HCV GT1b preceding that of GT1a by 15–17 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylodynamic analysis was performed on concatenated NS3, NS5A, and NS5B sequences of every patient in order to increase the confidence of inferred evolutionary relationships. Several studies have tried to reconstruct the origin and evolutionary history of the most common epidemic HCV subtypes such as GT1a, GT1b, and GT3a [ 4 , 32 , 50 , 56 , 57 , 58 , 59 ]. A study by Margiokinis et al (2009) supports a massive expansion of the GT1a and GT1b epidemics between 1940 and 1980, with the expansion of HCV GT1b preceding that of GT1a by 15–17 years.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that last common ancestor of Gt1a sequences dates around 1960 (95% HPD, 1911-1994), a period of the post-World War II and Cold War-era migrations. Hoshino et al (2018) found the increase of GT1a population in Okinawa, Japan in two periods-from 1965 to 1980, which could be attributed to the US occupation after World War II and in the beginning of the 21st century which could be associated with an increase in the illicit drug use [59]. The Bayesian skyline analysis of Croatian GT1a sequences revealed an exponential increase of HCV GT1a infections in the 1990s and its continued growth throughout the first decade of the 2000s, which is in accordance with a huge increase in the number of IDU registered in this period in Croatia [60].…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic tree for HCV 1a NS5A sequences (1126 nucleotides, positions 6330-7455 according to HCV 1a reference strain H77 (GenBank NC004102)), built under a GTR model; branches with group reliability >90% are indicated in red; HCV 1a sequences from this study are indicated in blue; the type of RAS (M28V) or wild-type (WT) are indicated for each sequence. HCV1a sequences from Japan [20] are indicated in green. Sequences isolated from the intravenous drug users marked as IDUs.…”
Section: Prevalence Of Rassmentioning
confidence: 99%
“…Clinically relevant amino acid residue in position 28 was found to form covariance network with amino acid residues in positions 78, 308, and 372 ( Figure 3e). To check if these effects are valid for a different set of sequences, we have built a covariance network for sequences from the case of HCV 1a introduction into Japan [20] (marked in green on phylogenetic tree in Figure 2). This Japanese sequence set was rich in M28V RAS (19.2%; 5/26), although not as rich as the Russian set (57,2%, 11/19; Figure 1).…”
Section: Covariance Of Ras With Other Amino Acid Residues Within Ns5amentioning
confidence: 99%
“…We and others have conducted clinical studies in patients with symptoms of autoimmune liver disease[1], hepatitis C[2,3], bacterial infection[4], acute liver failure liver[5], nonalcoholic fatty liver disease[6] and cirrhosis. We have also conducted translational research that bridges basic research using hematopoietic cells[7-14], hepatic stellate cells (HSCs)[15-18], embryonic stem cell-derived hepatocytes[19-22], bioartificial livers[23-26], animals[27-33] and clinical research in humans.…”
Section: Introductionmentioning
confidence: 99%